Mutualism and Entrepreneurial Coexistence as Catalysts for Family Businesses Sustainability - Fahrul Riza; Teofilus; Yoseva Maria; Metta Padmalia (Universitas Medan Area, 2025)
Family-based companies are the pillars of the economy in many countries, but many fail to survive. Based on the theory of business symbiosis, this study investigates the influence of mutualism and entrepreneurial coexistence on the sustainability of family businesses. The study uses quantitative methods. A total of 210 respondents were selected using convenience non-random sampling techniques. Data were analyzed using a covariance-based structural equation model. The results of hypothesis testing prove that a significant influence exists between variables, and entrepreneurial coexistence partially mediates the influence of mutualism on the sustainability of family businesses. Mutualism fosters a collaborative environment that, in turn, positively impacts family business performance. Establishing clear boundaries between family, ownership, and business matters, encouraging open communication, and promoting professional development among family and non-family personnel are all key elements toward sustaining a successful symbiotic relationship. From a practical standpoint, family enterprises must actively manage the inherent tension between emotional attachment and professionalism. Expanding family-business symbiosis theories show how mutualism and entrepreneurial coexistence maintain advantageous dynamics in family enterprises, improving sustainable family operations. Our research emphasizes the work of the theory of family business symbiosis as an alternate theory for sustaining family enterprise.